Temporal and spatial variability of sympagic metazoans in a high-Arctic fjord, Svalbard - Pitusi, Vanessa; Gradinger, Rolf; Søreide, Janne E. (Frontiers in Marine Science, 2023)
Svalbard is one of the fastest warming regions in the Arctic including massive loss in fjord sea ice both in terms of area coverage, ice thickness and duration. Sea ice is a habitat for a wide variety of microscopic flora and fauna, and we know little about the impact of accelerated loss of sea ice on this unique sea ice community. Here, we present the first study on the seasonal progression and spatial distribution of the sympagic meiofauna community, in a Svalbard fjord. Further, the meiofauna community in sea ice versus the water column below were compared to investigate the link between the two habitats. In total, we found 12 taxa associated with the sea ice and 15 taxa in the water column below with 11 taxa occurring in both habitats. However, a Canonical-analysis (CA) showed that despite similarities in taxa the two mediums were distinctly different (potentially) due to the low abundance of ice nematodes and polychaete juveniles, in pelagic samples. Temporally, ice meiofauna abundances ranged from 9.7 to 25.3 x 103 ind m-2 from beginning of March to end of April, following the seasonal build-up of ice algal biomass from 0.02 to 15.99 mg Chl a m-2 during the same time span. For the transect stations, the lowest ice meiofauna abundance was recorded at the outermost station (VMF2) with 1.6 x 103 ind m-2 and the highest abundance at the mid-station MS with 25.3 x 103 ind m-2. Our results indicate that fjord ice harbours most ice algae and sympagic meiofauna in its lower 10-cm with highest values in the lowermost 2-cm, at the sea ice water interface. Sympagic meiofauna communities were mostly dominated by nematodes or polychaete juveniles. We observed the phenology of ice nematodes through the maturation of females and hatching of juveniles from eggs. Polychaete larvae developed (quickly) into juveniles and grew morphological features indicative of readiness for settlement. Thus, we propose, that as with other parts of the Arctic, sea ice in Svalbard fjords plays an important role in the life cycle of ice nematodes and for accelerating the growth of polychaete larvae.